2020
DOI: 10.1038/s41598-020-75451-5
|View full text |Cite
|
Sign up to set email alerts
|

Deep phenotype unsupervised machine learning revealed the significance of pachychoroid features in etiology and visual prognosis of age-related macular degeneration

Abstract: Unsupervised machine learning has received increased attention in clinical research because it allows researchers to identify novel and objective viewpoints for diseases with complex clinical characteristics. In this study, we applied a deep phenotyping method to classify Japanese patients with age-related macular degeneration (AMD), the leading cause of blindness in developed countries, showing high phenotypic heterogeneity. By applying unsupervised deep phenotype clustering, patients with AMD were classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…pachychoroid diseases are common. 14,41 Subsequent studies also support this idea, and the criteria for a thick choroid currently are the subject of debate. 37,42,43 However, despite the increasing clinical importance of the choroid, only a few large-scale cohort studies have provided normative data for choroidal thickness.…”
Section: Discussionmentioning
confidence: 97%
“…pachychoroid diseases are common. 14,41 Subsequent studies also support this idea, and the criteria for a thick choroid currently are the subject of debate. 37,42,43 However, despite the increasing clinical importance of the choroid, only a few large-scale cohort studies have provided normative data for choroidal thickness.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, this can be a clear limitation of the current study since there can be overlap of SFCT between pachychoroid and nonpachychoroid eyes. 32 Third, there was a significant difference in age and sex distribution between pachychoroid and nonpachychoroid eyes both in the dataset and test set. However, we believe this will not significantly affect clinical application of the models since younger age and male prominence are well-established features of pachychoroid and also should be observed in real life.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, Hosoda et al used machine learning to review Japanese patients with AMD and suggested that 46% of cases were reclassi ed as PNV. 22 However, the diagnosis criteria for PNV have not been clearly determined. Thus, we employed the de nition criteria of previous reports 18, 23 and found a strong correlation between CCT and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…According to the recent reports on PNV analysis, 18,19,22,23,25,31 we diagnosed a patient as PNV when all following criteria were satis ed: Type1 CNV (including PCV), CVD ≥ 180 µm, CCT ≥ 220 µm, absence of drusen in the fundus photographs, and increased choroidal vascular permeability in the late phase of the ICGA images (Fig. 3).…”
Section: Methodsmentioning
confidence: 99%